Beliefs about Social Distancing During COVID-19 Stay-At-Home Orders: A Theory-Based Salient Belief Elicitation - Christopher Owens; Nicole Struble; Joseph M. Currin; Zachary Giano; Randolph D. Hubach (New Prairie Press, 2021)
Understanding the beliefs about social distancing behaviors is required to inform 2019 coronavirus disease (COVID-19) interventions that are based on theory, research, and evidence. This study investigated the salient beliefs related to social distancing. United States adults (n= 106) recruited from Amazon's Mechanical Turk completed an online reasoned action approach belief elicitation from April 19 to April 25, 2020. Behavioral beliefs (advantages and disadvantages), normative beliefs (approvers and disapprovers), and control beliefs (facilitators and barriers) related to social distancing were elicited via open-ended questions. A content analysis was performed, and kappa statistics revealed high levels of interrater reliability (α = 0.86-0.96). Results revealed that a perceived salient advantage to social distancing was individual COVID-19 prevention, more so than community prevention. The most cited disadvantage was that social distancing could prevent participants from socially interacting with others, which could negatively impact mental health. Family and friends were the most mentioned approvers, while people who hold conservative ideologies and negative attitudes about COVID-19 were the most frequent disapprovers. Supply accessibility and store policies were the most listed facilitators. Results suggest three implications. First, pandemic-related public health and social marketing campaigns should focus more on individual health benefits than community health benefits. Second, digital public health interventions that address social connectedness and mental health outcomes are critical during pandemics. Third, public health scientists and practitioners should work with local and national media outlets and political leaders to create community-tailored and evidence-based information to increase adherence of mitigation strategies.